Analisis Fasilitas dan Kualitas Pelayanan terhadap Kepuasan Pelanggan di SPBU 53.612.67 - Daniel Budiyanto; Agung Dwi Nugroho (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study aims to examine the role of facilities and service quality in influencing customer satisfaction at SPBU (gas station) 53.612.67 Arteri Baru Porong. As fuel remains a primary energy source for transportation, the availability and functionality of SPBUs are essential to support daily mobility. The research adopts a qualitative descriptive approach through in-depth interviews with selected SPBU customers using purposive sampling. Findings reveal that both the completeness and convenience of facilities, along with the quality of service provided by staff, significantly impact customer satisfaction. Well-maintained amenities such as restrooms, prayer rooms, and rest areas, combined with prompt and friendly service, enhance the overall customer experience. These results highlight the importance of continuous improvement in service delivery and facility maintenance as strategic efforts to strengthen customer loyalty and improve SPBU competitiveness in the energy sector.